Relasi Manusia dan Ternak dalam Perspektif Budaya: Studi Kasus Praktik Pemberian dan Pemilihan Nutrisi Pakan Ternak di Komunitas Agraris di Desa Matahora Kabupaten Wakatobi - Hajar Hajar (FKIP UNSULTRA, 2025)
In the context of agrarian communities in Indonesia, the relationship between humans and livestock is not solely based on economic value but also reflects social, symbolic, and cultural relationships. This study aims to examine how the practice of providing and selecting livestock feed nutrients in Matahora Village, Wakatobi Regency, is influenced by local cultural values that exist within the agrarian community. This research uses a literature study approach by analyzing previous works on the relationship between humans and livestock, local wisdom in livestock husbandry, and culturally based agricultural practices. The results of the study indicate that the community in Matahora Village has developed a pattern of livestock feed selection that considers not only nutritional aspects but also local beliefs regarding plant properties, feeding timing, and certain taboos. For example, lamtoro leaves are believed to strengthen livestock bones, while the provision of cassava leaves is restricted because they are considered symbolically